2014
DOI: 10.1021/la501160s
|View full text |Cite
|
Sign up to set email alerts
|

The Headgroup (A)Symmetry Strongly Determines the Aggregation Behavior of Single-Chain Phenylene-Modified Bolalipids and Their Miscibility with Classical Phospholipids

Abstract: In the present work, we describe the synthesis of two single-chain phenylene-modified bolalipids, namely PC-C17pPhC17-PC and PC-C17pPhC17-OH, with either symmetrical (phosphocholine) or asymmetrical (phosphocholine and hydroxyl) headgroups using a Sonogashira cross coupling reaction as key-step. The temperature-dependent aggregation behavior of both bolalipids in aqueous suspension was studied using transmission electron microscopy (TEM), differential scanning calorimetry (DSC), Fourier-transform infrared (FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 52 publications
6
41
0
Order By: Relevance
“…This behaviour indicates the formation of nanofibres, which in turn immobilize the solvent molecules and allow the formation of a transparent hydrogel. A similar observation was found for PC-C17pPhC17-PC [35] and also for phenylene-free analogues, such as PC-Cn-PC with alkyl chain lengths ranging from n = 22–36 [2426 38,40]. …”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This behaviour indicates the formation of nanofibres, which in turn immobilize the solvent molecules and allow the formation of a transparent hydrogel. A similar observation was found for PC-C17pPhC17-PC [35] and also for phenylene-free analogues, such as PC-Cn-PC with alkyl chain lengths ranging from n = 22–36 [2426 38,40]. …”
Section: Resultssupporting
confidence: 80%
“…The results obtained were compared to PC-C17pPhC17-PC [35] and PC-C16pPhC16-PC [36], structural analogues with slightly shorter alkyl chains, and the homologous series of phenylene-free PC-Cn-PC, with n = 22–36 [2426 38,40]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we showed that the headgroup asymmetry strongly influences the aggregation behavior of single-chain bolalipids. 32,33 The new bolalipids contain a membrane-spanning C32 alkyl chain that is bound with one end to the sn-3 position of a glycerol unit whereas the other end carries only a hydroxyl group. The sn-2 position of the glycerol moiety is etherified with either a hexadecyl (lipid I) or a racemic 10-methylhexadecyl (lipid II) residue ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%